The assessment of marine bioinvasion diversity and history - Carlton, James T. (2023)
A significant challenge in comparing and contrasting regional reviews of non-native marine species diversity is that evaluation methods vary widely, resulting in highly inconsistent taxonomic, habitat and historical coverage even in ostensibly well-studied regions. It is thus difficult to interpret whether strikingly different numbers of non-native species in different regions reflect differential invasion patterns or different assessment criteria and capabilities. We provide a comprehensive guide to the methods and techniques to assess the diversity and timing history of non-native and cryptogenic marine species. We emphasize the need to broaden taxonomic and habitat breadth when documenting invasions, to use a broader and deeper search term menu (including using older terms), to thoroughly access global systematic and invasion literature for local, regional records, and to delve deeper into invasion timing to avoid the use of dates-of-publication to assess invasion tempo and rates. Fundamental in all invasions work is the reassessment of the status of ostensibly native species which in fact may have been introduced decades or centuries earlier. We expand to 14 categories the criteria for the recognition of non-native species. Without thorough and vetted modern and historical assessments of the scale of invasions across temperate, subtropical, and tropical marine ecosystems, our ability to look deep into marine community ecology, evolution, and biogeography is strikingly compromised, as is our ability to frame robust invasion policy and management plans.